1996
DOI: 10.1111/j.1600-0765.1996.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical study of nerve fibers containing substance P in the junctional epithelium of rats

Abstract: Nerve fibers with substance P-like immunoreactivity (SP-IR) in the junctional epithelium (JE) of 32-42-d-old rats were examined by both light and electron microscopy using the avidin-biotin-peroxidase complex method. The density of nerve fibers with SP-IR was highest in the middle portion of the JE; however, a few fibers were localized in the coronal portion of the JE and close to the enamel surface. Also, rich innervation was found especially in the basal cell layer of the JE. Unmyelinated axons with SP-IR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…A number of regenerative nerve fibers were also evident. These had invaded the superficial layer of the peri-implant epithelium in a manner similar to the invasion into the junctional epithelium as described by Tanaka et al All of these regenerative nerve fibers possess free endings, and their functions might be a sensory system for pain, touch and pressure (27). We suggest that these free nerve endings play a role not only in the sensory system but also as part of the defense system, even though Merkel cells do not regenerate after implantation.…”
Section: Behavior Of the Peri-implant Epithelium And Nerve Endingsmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of regenerative nerve fibers were also evident. These had invaded the superficial layer of the peri-implant epithelium in a manner similar to the invasion into the junctional epithelium as described by Tanaka et al All of these regenerative nerve fibers possess free endings, and their functions might be a sensory system for pain, touch and pressure (27). We suggest that these free nerve endings play a role not only in the sensory system but also as part of the defense system, even though Merkel cells do not regenerate after implantation.…”
Section: Behavior Of the Peri-implant Epithelium And Nerve Endingsmentioning
confidence: 97%
“…However, Buser et al showed that there are wide intercellular spaces and transmigrating polymorpho-nuclear leukocytes and lymphocytes in the junctional epithelium around the implant surface (2). Concerning nerve fibers, Tanaka et al reported that many nerve fibers containing substance P are present in the middle portion of the junctional epithelium, whereas they are sparse in the oral sulcular epithelium and in the oral epithelium (27). They suggested that substance P, which is released from the nerve fibers into the junctional epithelium, might regulate the endocytotic activity of neutrophils and junctional epithelial cells to form a part of the defense network against noxious stimuli.…”
Section: Behavior Of the Peri-implant Epithelium And Nerve Endingsmentioning
confidence: 99%
“…These receptors are also localized in neutrophils invading into the intercellular spaces between PIE cells (Figure 8c). Overall, the PIE shows a similar distribution of substance P-containing sensory nerve fibers and their neurokinin-1 receptors, compared to junctional epithelium Tanaka et al, 1996;Kido et al, 1999). …”
Section: Innervation Of Pie By Sensory Nerve Fibersmentioning
confidence: 83%
“…The sensory nerve fibers contain the neuropeptides, calcitonin gene-related peptide (Byers et al, 1987;Nagata et al, 1992Nagata et al, , 1994 and substance P (Nagata et al, , 1994Tanaka et al, 1996;Kido et al, 1999), and terminate close to endothelial cells, neutrophils, and junctional epithelial cells Tanaka et al, 1996). The peri-implant mucosa is also supplied with sensory nerves containing calcitonin generelated peptide (Fujii et al, 2003) and substance P (Yamaza et al, 2009) (Figure 7a).…”
Section: Innervation Of Pie By Sensory Nerve Fibersmentioning
confidence: 99%
See 1 more Smart Citation